2012 Spillover Report : Background Papers. (Policy Papers; Policy Paper ;, 2012)
This note conducts a business cycle accounting analysis for systemic economies, with an emphasis on spillover effects from macroeconomic versus financial shocks. The systemic economies under consideration are China, the Euro Area, Japan, the United Kingdom, and the United States. This analysis is based on historical decompositions of output growth derived from the estimated structural macroeconometric model of the world economy, disaggregated into thirty five national economies, documented in Vitek (2012). Within this framework, each economy is represented by interconnected real, external, monetary, fiscal, and financial sectors. Spillovers are transmitted across economies via trade, financial, and commodity price linkages.